Respon Gulma dari Kedelai Akibat Perlakuan Dosis dan Waktu Aflikasi Glifosat - Basyir Basyir (Jurnal Agripet, 2001)
ABSTRACT.The responds of weed and soybean by gluphosate dosage and time application research was conducted Experimental Farm, Syiah Kuala University since June to September 1999. The research was designed according to Completely Randomize Design. The aimed of the research is to know weed and soybean respons by glyphosate dosage and time application. The result shown that the glyphosate dosage had significant effect on weed control efficiency but hat no effect to soybean growth and yield. For the time of glyphosate application show that significant effect to number of grain, grain dry weight, but hat no significant effect to weed control efficiency and number of pod.